Integrity and characteristics of the bones of the Danish King St Knud (II) the Holy (†AD 1086) - L., Kaare; Bennikke, Pia; Kjær, Ulla; Rahbek, Uffe (Journal of Danish Archaeology, 1997)
Integrity and characteristics of the bones of the Danish King St Knud (II) the Holy (†AD 1086)